From Chilean saltpeter to modern agriculture: navigating nitrate toxicity in ruminants through compartmental modeling - I. Ya. Oliynyk (Біологія тварин)
Nitrate/nitrite poisoning is a significant issue in ruminant livestock health, with historical roots predating the widespread use of nitrogen fertilizers. This review explores the various factors contributing to nitrate toxicity, including natural and anthropogenic sources, metabolic pathways, mechanisms of action, and the variability in reported data. The importance of compartmental modeling in understanding nitrate metabolism dynamics is emphasized. These models provide a framework for simulating the complex processes involved in nitrate intake, conversion, absorption, distribution, and excretion, ultimately informing effective mitigation strategies. The goal of this article is to provide a comprehensive overview of nitrate/nitrite poisoning in ruminants and highlight the role of compartmental modeling in safeguarding animal health, optimizing agricultural practices, and ensuring food safety in the context of modern agriculture.